2012
DOI: 10.1128/aac.05583-11
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Emerging Carbapenemase NDM-1 with a Bleomycin Resistance Protein in Enterobacteriaceae and Acinetobacter baumannii

Abstract: The carbapenemase NDM-1 has been identified recently in Enterobacteriaceae and Acinetobacter baumannii as a source of multidrug resistance, including resistance to carbapenems. By analyzing the immediate genetic environment of the bla NDM-1 carbapenemase gene among a series of NDM-1-producing enterobacterial isolates, a novel gene (ble MBL , for ble gene associated with the metallo-␤-lactamase NDM-1) was identified. The ble MBL gene encodes a novel bleomycin resistance protein (BRP), named BRP MBL , that share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 30 publications
(32 reference statements)
9
62
0
1
Order By: Relevance
“…PCR mapping was performed to identify the genetic sequences surrounding the bla NDM-1 gene in all positive isolates. The same structure was found, with the bla NDM-1 gene preceded by a truncated version of ISAba125, followed by the ble MBL gene encoding resistance to bleomycin (25). Similar structures were identified previously in different species from different countries (19).…”
supporting
confidence: 63%
“…PCR mapping was performed to identify the genetic sequences surrounding the bla NDM-1 gene in all positive isolates. The same structure was found, with the bla NDM-1 gene preceded by a truncated version of ISAba125, followed by the ble MBL gene encoding resistance to bleomycin (25). Similar structures were identified previously in different species from different countries (19).…”
supporting
confidence: 63%
“…3). It was reported that bla NDM-1 and ble MBL are under the control of the same promoter in front of bla NDM-1 , and this structure may facilitate the spread of NDM-1 when under the selective pressure of bleomycin-like mol- ecules in the environment (38). The entire ISAba125 element was detected immediately upstream of the bla NDM-1 gene in each of the 16 isolates.…”
Section: Resultsmentioning
confidence: 88%
“…CP000649.1). Notably, the bla NDM-1 gene environment is adjacent to a bleomycin resistance protein-encoding gene, a finding that is common in bla NDM-1 -producing strains and is thought to impact the overall survival value of this strain (15).…”
Section: Patientsmentioning
confidence: 99%